Environmental Implications of Multi-Level Governance Failures in Perusahaan Listrik Negara (PLN) De-dieselization Program: Evidence from Isolated Power Systems in the frontier, outermost, and underdeveloped (3T) regions of Indonesia - Silviana Silviana; Singgih Saptadi; Buchari Zainal Arifin; Marcelinus Christwardana (Journal of Bioresources and Environmental Sciences, 2025)
Indonesia’s commitment to achieve Net Zero Emissions (NZE) by 2060 requires substantial decarbonization of its electricity sector, including the phase-out of diesel-based isolated power systems in remote and underdeveloped regions (3T regions). While de-dieselization programs have been widely promoted as a technically and economically feasible solution, their environmental performance remains uneven. This study examines Indonesia’s de-dieselization program implemented by PT PLN (Persero) through the lens of Multi-Level Governance (MLG), focusing on how governance dynamics shape the realization of emission reduction benefits. Using a qualitative research design, this study integrates document analysis, in-depth interviews with national, corporate, regional, and community-level actors, and secondary data-based carbon emission estimation. The findings reveal persistent governance failures manifested as policy misalignment, overlapping mandates, and accountability gaps across governance levels. These failures delay project implementation, prolong diesel operations, and generate a systemic “environmental performance gap,” where planned emission reductions are not fully realized. Carbon estimation indicates that delayed or incomplete de-dieselization results in the loss of significant mitigation opportunities, amounting to hundreds of thousands of tons of CO₂ annually. The study contributes to the energy transition literature by conceptualizing emission reduction as a governance-dependent outcome rather than an automatic result of technology substitution. Policy implications emphasize the need to embed environmental performance indicators explicitly into governance frameworks and to strengthen cross-level accountability to ensure that de-dieselization delivers tangible climate benefits in isolated power systems.